COMMUNITY PARTICIPATION IN INCREASING TOURISM VILLAGES: PARTISIPASI MASYARAKAT DALAM PENINGKATAN DESA WISATA - Ginung Pratidina; wahyudin, cecep; Neng Virly Apriliyani; Nadia Amalia (Universitas Djuanda, 2023)
Community participation has an important role in being involved in the management of a tourist village, if the tourism village is managed properly by the community, the tourism village in Kabandungan village can attract tourists to visit it so that the surrounding community can feel the benefits. The purpose of this community service is intended to provide counseling on community participation in improving tourism villages in Kabandungan village which have the potential to be developed so as to increase people's income. The activity method used is counseling, observation, Focus Group Discussion (FGD) as well as pretest and posttest. The results in this service show that there is an increase in knowledge in the community to develop and improve further tourism villages. In the sense that the community has a high awareness of the potential of the village they have so that in the future it can increase people's income with an increase in tourism villages.